DLX6-AS1: A Long Non-coding RNA With Oncogenic Features - Ghafouri-Fard, Soudeh; Najafi, Sajad; Hussen, Bashdar Mahmud; Ganjo, Aryan R.; Taheri, Mohammad; Samadian, Mohammad (Frontiers in Cell and Developmental Biology, 2022)
Long non-coding RNAs (lncRNAs) are a heterogeneous group of ncRNAs with characteristic size of more than 200 nucleotides. An increasing number of lncRNAs have been found to be dysregulated in many human diseases particularly cancer. However, their role in carcinogenesis is not precisely understood. DLX6-AS1 is an lncRNAs which has been unveiled to be up-regulated in various number of cancers. In different cell studies, DLX6-AS1 has shown oncogenic role via promoting oncogenic phenotype of cancer cell lines. Increase in tumor cell proliferation, migration, invasion, and EMT while suppressing apoptosis in cancer cells are the effects of DLX6-AS1 in development and progression of cancer. In the majority of cell experiment, mediator miRNAs have been identified which are sponged and negatively regulated by DLX6-AS1, and they in turn regulate expression of a number of transcription factors, eventually affecting signaling pathways involved in carcinogenesis. These pathways form axes through which DLX6-AS1 promotes carcinogenicity of cancer cells. Xenograft animal studies, also have confirmed enhancing effect of DLX6-AS1 on tumor growth and metastasis. Clinical evaluations in cancerous patients have also shown increased expression of DLX6-AS1 in tumor tissues compared to healthy tissues. High DLX6-AS1 expression has shown positive association with advanced clinicopathological features in cancerous patients. Survival analyses have demonstrated correlation between high DLX6-AS1 expression and shorter survival. In cox regression analysis, DLX6-AS1 has been found as an independent prognostic factor for patients with various types of cancer.